Monitoring of Atrazine in Surface Waters of an Agroecosystem in the Province of Córdoba (Argentina) Using an Immunoassay Technique - Garcia, Mariana; Lutri, Veronica; Blarasin, Monica; Matteoda, Edel; Bettera, Susana (International Journal For Research In Agricultural And Food Science, 2019)
Although the use of atrazine has been banned and restricted in several parts of the world, in Argentina this herbicide is still being used. The atrazine detection was made with a fast and relatively cost-effective immunoassay test whose major advantage lied in its ability to quantify with high accuracy both atrazine and its main metabolite, a useful aspect for monitoring and regulatory programs. The atrazine values found in surface water (0.05– 15.6 µg/L) and rainwater (0.23 – 0.73 µg/L) is an undeniable indicator of the impact that agricultural activities generate on the water resource in the Aeolian fluvial plain of Argentina. The major values were detected in the humid periods which also coincides with the herbicide application time.